Sedimentology of Potential Tertiary Fluvial Deposits in Kluang, Johor, Malaysia - Choong Chee Meng, Nur Huda M Jamin, Muhammad Azfar Mohamed, Chin, . (2017)
The occurrences of Tertiary basins in Peninsular Malaysia are localized and limited. Commonly, their boundaries are difficult to define due to limited exposure. They are sometimes difficult to be differentiated from the younger Quaternary alluvium. Hence, the geological knowledge for the most Tertiary basins of the Peninsular Malaysia is not well developed. In this study, two new outcrops with potential Tertiary formation were visited and described in terms of sedimentology.